VD_FINDINFO HC / 2012 / 572 vom 4. September 2012 - VD Tribunal cantonal (2012)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, RELATIONS PERSONNELLES | 176 al. 1 ch. 1 CC, 176 al. 3 CC, 273 CC